The GPCR A35 regulates fecundity of Nilaparvata lugens Stål via juvenile hormone signaling - Cao, Minjuan; Deng, Di; Mao, Ziyue; Duan, Zhirou; Sun, Yuhang; Zhao, Xudong; Ge, Linquan (Frontiers in Insect Science, 2025)
The brown planthopper, Nilaparvata lugens is a major rice pest in Asia, with its high fecundity contributing to recurrent outbreaks. G protein-coupled receptors (GPCRs) are a critical class of transmembrane proteins in insects that sense diverse extracellular and intracellular signals and regulate a wide range of physiological processes. In this study, we characterized GPCR A35 and its function in N. lugens fecundity. Expression profiling revealed that GPCR A35 was highly enriched in female heads and fat bodies, with peak levels in females at 4 days post-eclosion. RNAi-mediated the silencing of GPCR A35 in fifth-instar nymphs by 57–60%, and was effectively delivered to female adults, resulting in a 14.8% reduction in juvenile hormone (JH) titer and marked downregulation of JH biosynthetic and signaling genes, including HMGCR (−60.1%), FPPS (−57.0%), JHAMT (−52.7%), Met (−24.2%), and Kr-h1 (−78.3%). Silencing of GPCR A35 further decreased Vg and VgR expression by 82.1% and 72.9% in females at 4 days post-eclosion, reduced protein contents in fat body and ovaries, and impaired ovarian development with fewer mature oocytes. Consequently, female fecundity declined by 51.3%, oviposition duration shortened by 18.5%, and the F1 population growth index decreased by 46.8%. These results demonstrate that GPCR A35 regulates fecundity in N. lugens by modulating JH-mediated vitellogenesis and oogenesis, providing a novel molecular target for RNAi-based green pest control.